2018
DOI: 10.1186/s40851-018-0110-2
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the muscular system in tetrapod limbs

Abstract: While skeletal evolution has been extensively studied, the evolution of limb muscles and brachial plexus has received less attention. In this review, we focus on the tempo and mode of evolution of forelimb muscles in the vertebrate history, and on the developmental mechanisms that have affected the evolution of their morphology. Tetrapod limb muscles develop from diffuse migrating cells derived from dermomyotomes, and the limb-innervating nerves lose their segmental patterns to form the brachial plexus distall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 262 publications
(249 reference statements)
1
24
0
Order By: Relevance
“…The MMP cells that will form the pectoral fin musculature become divided into two dorsally and ventrally oriented clusters, which will develop into the abductor and adductor muscle respectively. The mechanism behind this division remains unresolved and seem to differ among different vertebrate groups [30]. We found that pelvic fin muscle was missing in zebrafish met -/- mutants and we also observed a drastic reduction of pectoral fin muscle, particularly in the abductor muscle of the pectoral fins (Fig 2 and Fig 3).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The MMP cells that will form the pectoral fin musculature become divided into two dorsally and ventrally oriented clusters, which will develop into the abductor and adductor muscle respectively. The mechanism behind this division remains unresolved and seem to differ among different vertebrate groups [30]. We found that pelvic fin muscle was missing in zebrafish met -/- mutants and we also observed a drastic reduction of pectoral fin muscle, particularly in the abductor muscle of the pectoral fins (Fig 2 and Fig 3).…”
Section: Discussionmentioning
confidence: 65%
“…Forelimb or hindlimb patterning is determined by homeobox factor Pitx1 and the T-box factors tbx4 and Tbx5 [28, 29]. During the migration from the somite MMP cells will receive signals from the lateral plate mesenchyme and become divided into dorsal and ventral subclusters that will give rise to the abductor and adductor muscle respectively [30].…”
Section: Introductionmentioning
confidence: 99%
“…Together with expansion of the endochondral bone, the architecture of muscles and nerves also changes in the type III pectoral fin. The neural and muscular pattern of type III resembles that of limbs (Hirasawa and Kuratani 2018), such that the sarcopterygian fin resembles the hypothetical precursor for the tetrapod limb.…”
Section: Fin-to-limb Transition From the Viewpoint Of Morphologymentioning
confidence: 93%
“…Recently it has been proposed that the appearance of the brachial plexus was an evolutionary innovation in tetrapods (Hirasawa & Kuratani, 2018), which was most likely associated with the appearance of this well-defined cervical region. In elasmobranch fish -such as sharks and rays -the pectoral fin muscles are innervated directly by branches of the spinal nerves.…”
Section: Entepicondylar Foramenmentioning
confidence: 99%
“…However, the muscles of the anterior limbs of tetrapods are innervated by, at most, seven nerves. In tetrapods, the brachial plexus typically consists of a set of spinal nerves around the cervicothoracic boundary of the axial system and most of the limb muscles are innervated by nerve fibres comprising two or more plexus roots (Hirasawa & Kuratani, 2018). This structure is exclusive to tetrapods, suggesting that the brachial plexus was an evolutionary novelty of the clade.…”
Section: Entepicondylar Foramenmentioning
confidence: 99%